PELATIHAN MANAJEMEN PAKAN DAN PEMELIHARAAN KAMBING PERANAKAN ETAWA UNTUK MENINGKATKAN KINERJA PETERNAK DIPETERNAKAN AZHAR FARM PAYAKUMBUH - Rizqan Rizqan; Elly Roza; Hilda Susanty; Linda Suhartati; Ananda Ananda (Jurnal Hilirisasi IPTEKS, 2024)
Goats are one of the small ruminants as meat and milk producers (dual-purpose), but cow's milk is widely sold in the market. Goat milk is no less nutritious than cow's milk; besides having an advantage in protein content, goat milk also contains more vitamins A and B (especially riboflavin and niacin). One of the goats widely cultivated by farmers and utilized as a source of animal protein, meat, and milk is the Ettawa crossbred goat. As researchers have widely reported, the potential of Ettawa crossbred goats is that milk producers are still very diverse, ranging between 0.45 and 2.2 kg/head/day. This is generally caused by maintenance management, which still needs to be improved. The purpose of this service is to counsel Azhar Farm farms on the management of raising Ettawa crossbred goats to get maximum productivity. The methods used are counseling, training, coaching, discussion, and evaluation of service activities. The activity results include improving farmers' ability to apply the management of raising Ettawa crossbred goats, which are dairy-type goats (milk producers), and increasing their productivity. It is hoped that this activity can motivate farmers to develop their livestock business to improve livestock health, increase population, increase production, and increase income for farmers.